Unrecoverable Past and Uncertain Present: Speculative Drama’s Fictional Worlds and Nonclassical Scientific Thought - Derek, Gingrich (Université d'Ottawa / University of Ottawa, 2014)
The growing accessibility of quantum mechanics and chaos theory over the past eighty years has opened a new mode of world-creating for dramatists. An increasingly large collection of plays organize their fictional worlds around such scientific concepts as quantum uncertainty and chaotic determinism. This trend is especially noticeable within dramatic texts that emphasize a fictional, not material or metafictional, engagement. These plays construct fictional worlds that reflect the increasingly strange actual world. The dominant theoretical approaches to fictional worlds unfairly treat these plays as primarily metafictional texts, when these texts construct fictional experiences to speculate about everyday ramifications of living in a post-quantum mechanics world. This thesis argues that these texts are best understood as examples of speculative fiction drama, and they speculate about the changes to our understanding of reality implied by contemporary scientific discoveries. Looking at three plays as exemplary case studies—John Mighton’s Possible Worlds (1990), Tom Stoppard’s Arcadia (1993), and Tony Kushner’s Homebody/Kabul (2001)—this thesis demonstrates that speculative fiction theories can be adapted into fictional worlds analysis, allowing us to analyze these plays as fiction-making texts that offer nonclassical aesthetic experiences. In doing so, this thesis contributes to speculative fiction studies, fictional worlds studies, and the dynamic interdisciplinary dialogue between aesthetic and scientific discourses.
Keywords: contemporary drama; Stoppard, Tom; speculative fiction; Kushner, Tony; fictional worlds; Mighton, John; possible worlds; theatre and philosophy; Homebody/Kabul; theatre and science; Arcadia; science and the arts